Aloe-vera leaf extract as a green agent for the synthesis of CuO nanoparticles inactivating bacterial pathogens and dye - Sharma, Saurabh; Kumar, Kuldeep (Journal of dispersion science and technology, 2021)
The present work describes the aloe-vera, as a green agent for the facile synthesis of copper oxide NPs and their deliberation for antibacterial and photocatalytic activities. The synthesis has been carried out at pH 11.5 and 70 °C with detailed characterization investigation through UV-spectroscopy, XRD (X-ray Diffraction), SEM (Scanning electron microscope), EDX (Energy-dispersive X-ray spectroscopy) and TEM (Transmission electron microscope) techniques. The study reveals the altered morphology of CuO NPs with a change in concentration of precursor. After characterization, CuO NPs with size 5-20 nm have been examined against pathogenic bacteria like Bacillus subtilis, Staphylococcus aureus, and Escherichia coli to calculate the zone of inhibition, MIC (minimum inhibitory concentration) and MBC (minimum bactericidal concentration). Photo-catalytic degradation has been performed in the presence of H 2 O 2 , which results in the degradation of MO (methyl orange) dye up to 96% in 24 min under exposure of UV light.